2007
DOI: 10.1002/jobm.200610274
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a phosphinothricin based herbicide on selected groups of soil microorganisms

Abstract: The effects of the herbicide glufosinate-ammonium on soil microbial populations and activity were observed in a laboratory microcosms over a 40 day period. Culturable aerobic bacteria, fungi and actinomycetes, the fundamental groups of heterotrophic microorganisms, were studied. Nitrifiers, considered a very sensitive group to these compounds were also evaluated. Since herbicides have been found to inhibit decomposition of cellulose in the soil, the effects of glufosinate on cellulolytic bacteria and fungi wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Only the highest concentration of metribuzin applied to the sandy soil had a stimulating effect. Similar responses were observed by Sebiomo et al (2011) in a study with atrazine, and by Pampulha et al (2007) in experiments with glufosinate-ammonium. However, Šantrić et al (2018) observed an elevated activity of dehydrogenase in a study with nicosulfuron and glyphosate in loamy and sandy soils.…”
Section: Discussionsupporting
confidence: 88%
“…Only the highest concentration of metribuzin applied to the sandy soil had a stimulating effect. Similar responses were observed by Sebiomo et al (2011) in a study with atrazine, and by Pampulha et al (2007) in experiments with glufosinate-ammonium. However, Šantrić et al (2018) observed an elevated activity of dehydrogenase in a study with nicosulfuron and glyphosate in loamy and sandy soils.…”
Section: Discussionsupporting
confidence: 88%
“…The more organic matter present in a soil, the longer an insecticide persists in it. According to several researchers [16,34,47,48,49,50], pesticides can cause qualitative and quantitative change in soil microbial populations.…”
Section: Effect Of Pesticides On Invertase On Different Days After mentioning
confidence: 99%
“…Being at the bottom of the food chain, changes in microbial communities are often a precursor to the changes in the health and viability of the environment as a whole [2]. Our conceptual and predictive understanding of soil ecosystem processes, functions and management can be enhanced only upon obtaining the knowledge about the microbial community structure and composition in a given region.…”
Section: Introductionmentioning
confidence: 99%